Characteristics of Rainfall-Discharge and Water Quality at Limboto Lake, Gorontalo, Indonesia - Subehi, Luki; Wibowo, Hendro; Jung, Kwansue (Journal of Engineering and Technological Sciences, 2016)
Problems of high turbidity, sedimentation, water pollution and siltation occur at Limboto Lake, Gorontalo, Indonesia. The objective of this study was to analyze the rainfall-discharge relationship and its implications for water quality conditions. Secchi disk (water transparency), chlorophyll-a (chl-a), and total organic matter (TOM) were measured in May 2012, September 2012 and March 2013 at three sites of the lake (L-1, L-2 and L-3) to observe the impacts on the surrounding catchment. Based on representative stations for rainfall data from 2004 to 2013, monthly averages of rainfall in March-May (166.7 mm) and September (76.4 mm) were used to represent the wet and dry period, respectively. Moreover, sediment traps at these three sites were installed in September 2012. Based on the analysis it is suggested that rainfall magnitude and land use change at the Alopohu River catchment influenced the amount of materials flowing into the lake, degrading the water quality. Specifically, the higher average rainfall in May (184.5 mm) gave a higher average total sediment load (4.41 g/L/day). In addition, water transparency decreased with increasing chl-a. This indicates that the concentrations of sediment and nutrients, reflected by the high amount of chl-a, influenced the water quality conditions.